Pay-As-They-Get-In: Attitudes Towards Migrants and Pension Systems - Tito Boeri; Matteo Gamalerio; Massimo Morelli; Margherita Negri (Institute of Labor Economics (IZA), 2023)
We study whether a better knowledge of the functioning of pay-as-you-go pension systems and recent demographic trends in the hosting country affects natives' attitudes towards immigration. In two online experiments in Italy and Spain, we randomly treated participants with a video explaining how, in pay-as-you-go pension systems, the payment of current pensions depends on the contributions paid by current workers. The video also explains that the ratio between the number of pensioners and the number of workers in their countries will grow substantially in the future. We find that the treatment improves participants' knowledge about how a pay-as-you-go system works and the future demographic trends in their country. However, we find that only treated participants who do not support populist and anti-immigrant parties display more positive attitudes towards migrants, even though the treatment increases knowledge of pension systems and demographic trends for all participants.
Keywords: C90; D83; H55; J15; F22; 330; information provision; experiment; immigration; pay-as-you-go pension systems; population ageing; populism